Leadership and change : a study of two South African peasant communities - Mafeje, Archie (Social Anthropology, 2016)
The fieldwork this thesis was carried out between the 8th December, 1962 and the 28th February, 1963 - an unusually short period by modern anthropological standards. The brevity of my intensive field being Xhosa-speaking, I had a previous knowledge of the two villages. As a small boy, I grew up in one of them (Gubenxa) and, as a student in the secondary school, travelled through the second one (All Saints) repeatedly. So I did not only have a fair idea about the: social system of the two villages, but also knew individual persons in them. This factor plus the fact that in both cases I was accommodated in the heart of the village added to the facility with which I was absorbed into the village life. I was with the villagers from dawn to midnight as a participant observer. My communication with them was direct, and this was enhanced by the fact that I spoke the same language as they and I had an adequate understanding of their cul¬tural background. My research techniques included attendance and observance of the different activities that took place in the village e.g. church assemblies, funeral or commemoration services, meetings at the head¬man's place, meetings of the various committees and recreational clubs, work-parties, bear-drinks, dances, women's gossip groups, and so on.